Preliminary study on designing and development of biogas analyser and monitoring system using IoT - Mohd Pu'ad, Muhamad Farhan; Sidek, Khairul Azami; Mel, Maizirwan (Penerbit Akademia Baru, 2018)
Today, IoT enables traditionally dumb physical devices be control wirelessly from great distance. Other than that, local biogas related research and industry has grown into a new level which requires biogas analyser for measuring the gas content. The analyser currently is imported from other countries at a very high cost due to no local production. It is not easy to request for customisation of the analyser from its supplier. Therefore, this study aims to prove possibility on developing a portable biogas analyser with a monitoring system using internet of things (IoT) approach. The system uses Raspberry Pi microcomputer as core of the design. The analyser is capable of measuring methane (CH4) and carbon dioxide (CO2) which are main composition of biogas. The system includes a web server to allow monitoring from a distance via smartphones, tablets, and personal computers using any browser with Internet connectivity. An experiment was conducted to test both sensors used in the analyser. Based on the experiment, both sensors show a positive but unstable response towards respective gases. Thus, the sensors are suitable to be used for the analyser with some adjustment on its stability and accuracy. Furthermore, the web server proves to be stable throughout the experiment. In future development, more additional features will be added to the current web server along with analyser’s case building and more experiments on the sensors. To summarize, this study shows it is possible to develop a biogas analyser with monitoring system using IoT approach locally which is still in progress. Moreover, with the success of this analyser in future, it will be a low-cost yet reliable alternative to the local researcher and industry.